Investment in Segmented Capital Markets - Nabi, Ijaz (Quarterly Journal of Economics, 1989)
This paper analyzes differences in the investment behavior of firms with unequal access to the capital market. Using empirical evidence from Pakistan, characteristics of formal and informal capital markets are described. Probabilities are estimated for firms being selected in the formal capital market where credit is cheap. Investment behavior is then analyzed using a switching regressions model. It is concluded that “favored” firms use more capital-intensive technologies and realize their investment plans more quickly than “excluded” firms do. Investment determinants related to entrepreneurial features are also identified.